Determinants of foreign direct investment in developing countries: 1990 - 2017 - ElShazly, Mona (AUC Knowledge Fountain, 2020)
This paper considers two important questions about FDI determinants: 1) what were the most important determinants that attracted FDI to developing countries in the top 20 FDI host countries between the years over the past three decades and 2) to evaluate whether FDI is more attracted to investment incentives or to the country's economic environment. Using a panel data with fixed effects model, we conclude that a country's economic environment is more important for FDI and that tax and tariff incentives are not significant factors for foreign investors when we control for macroeconomic variables.